COMBINATION OF MULTIMEDIAAPPLICATIONS AS AN INNOVATIVE PEDAGOGICAL TOOL OF A TEACHER AT A MARITIME HIGHER EDUCATIONAL INSTITUTION - Diagileva Олена; Leshchenko Альона; Paziak Алла; Yurzhenko Альона (Journal of Information Technologies in Education (ITE), 2021)
The article describes the development and active use of a combination of multimedia applications on the example of the Kherson State Maritime Academy. This study actually provides an understanding of the essence of the concept "combination of multimedia applications" as the integration, processing and at the same time reproduction of various means and methods of exchanging data, facts and information; reproduction of different types of electronic environments and signals. The latest research on the use of new technologies in education is analyzed: information and communication pedagogical environment, blended learning system, virtual / augmented / mixed reality technologies, gamification. Effective methods and modern multimedia distance learning tools are described in order to form general and professional competencies of teachers, future workers of sea and river transport in the conditions of the COVID-19 pandemic. It is emphasized that the main advantages of using the combination of multimedia applications in the system of higher maritime education are the expansion of educational opportunities, improvement of methods of access to new material and relevant information. The advantages of using LMS Moodle in the training of maritime specialists are described. It is emphasized LMS Moodle makes it possible to combine multimedia applications both on the basis of interaction and on the basis of use. The importance of using gamified elements to create educational content aimed at increasing the level of students’ motivation is indicated. The emphasis is placed on the use of the BigBlueButton online service by participants in the educational process in terms of distance learning. Examples of using BigBlueButton video conferencing platform are described. In conclusion, the authors emphasize the combination of different types and forms of activity makes the learning process more effective, as for a student with "clip" thinking constant change of activities gives a high quality result in terms of the learning material.